2023
DOI: 10.1027/0269-8803/a000307
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis and Systematic Review of Resting-State High-Frequency Heart Rate Variability in Binge-Eating Disorder

Abstract: Abstract. Binge-eating disorder (BED) is associated with a greater risk for cardiac problems and co-occurring health conditions. Resting-state measures of high-frequency heart rate variability (HF-HRV), which is a physiological proxy of self-regulatory neural functioning, may aid understanding of health risks. We systematically reviewed and meta-analyzed the literature on HF-HRV in individuals with BED and without BED. Six studies were reviewed in the qualitative synthesis, and five studies assessing HRV in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Jenkins et al (2021) reported increased parasympathetic and decreased sympathetic activity in AN as measured by HRV, EDA, and other PP (46 studies; N = 934). Three reviews found inconsistent results (HRV in BN [Peschel et al, 2016;17 studies;N = 1441], PP in acute stress in Binge eating disorder (BED) [Naish et al, 2019;14 studies], and HRV in BED [Christensen et al, 2023;6 studies;N = 153]). Burmester et al (2021) found no response in AN and increased aversive physiological responses to food stimuli in BN/BED (29 studies).…”
Section: Prior Reviewsmentioning
confidence: 99%
“…Jenkins et al (2021) reported increased parasympathetic and decreased sympathetic activity in AN as measured by HRV, EDA, and other PP (46 studies; N = 934). Three reviews found inconsistent results (HRV in BN [Peschel et al, 2016;17 studies;N = 1441], PP in acute stress in Binge eating disorder (BED) [Naish et al, 2019;14 studies], and HRV in BED [Christensen et al, 2023;6 studies;N = 153]). Burmester et al (2021) found no response in AN and increased aversive physiological responses to food stimuli in BN/BED (29 studies).…”
Section: Prior Reviewsmentioning
confidence: 99%
“…Other studies have investigated HRV and autonomic function in BED given their potential as risk markers for cardiac events. Meta-analysis of this data found no difference in resting state HRV between individuals with and without BED [ 70 ].…”
Section: Cardiovascular Complications In Other Eating Disorders: Buli...mentioning
confidence: 99%